Prevalence, risk factors and health outcomes associated with polypharmacy among urban community-dwelling older adults in multi-ethnic Malaysia - Lim, L.M.; McStea, M.; Chung, W.W.; Azmi, N.N.; Aziz, S.A.A.; Alwi, S.; Kamarulzaman, A.; Kamaruzzaman, S.B.; Chua, S.S.; Rajasuriar, R. (Public Library of Science, 2017)
Background Polypharmacy has been associated with increased morbidity and mortality in the older population. Objectives The aim of this study was to determine the prevalence, risk factors and health outcomes associated with polypharmacy in a cohort of urban community-dwelling older adults receiving chronic medications in Malaysia. Methods This was a baseline study in the Malaysian Elders Longitudinal Research cohort. The inclusion criteria were individuals aged ≥55years and taking at least one medication chronically (≥3 months). Participants were interviewed using a structured questionnaire during home visits where medications taken were reviewed. Health outcomes assessed were frequency of falls, functional disability, potential inappropriate medication use (PIMs), potential drugdrug interactions (PDDIs), healthcare utilisation and quality of life (QoL). Risk factors and health outcomes associated with polypharmacy (≥5 medications including dietary supplements) were determined using multivariate regression models. Results A total of 1256 participants were included with a median (interquartile range) age of 69(63± 74) years. The prevalence of polypharmacy was 45.9% while supplement users made up 56.9% of the cohort. The risk factors associated with increasing medication use were increasing age, Indian ethnicity, male, having a higher number of comorbidities specifically those diagnosed with cardiovascular, endocrine and gastrointestinal disorders, as well as supplement use. Health outcomes significantly associated with polypharmacy were PIMS, PDDIs and increased healthcare utilisation. Conclusion A significant proportion of older adults on chronic medications were exposed to polypharmacy and use of dietary supplements contributed significantly to this. Medication reviews are warranted to reduce significant polypharmacy related issues in the older population.